1985
DOI: 10.21236/ada156154
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of High-Resolution Gas Chromatography as Applied to the Analysis of Hydrocarbon Fuels and Other Complex Organic Mixtures. Volume 1

Abstract: Symmetric elution zone profile 3 Partially disengaged solute zones 4 Block diagram of basic systems approach 5 Three general forms of Chromatographie zone profiles Ig 6 Different combinations of solute zone profiles. 17 7 Rapidly generated chromatogram of a jet fuel. . 8 Chromatogram of a jet fuel obtained with a Pyrex glass open tubular column 9 Gaussian and exponentially modified Gaussian elution zone profiles 10 Series of normal paraffins eluted from a contaminated column 11 Elution behavior after removing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 217 publications
(242 reference statements)
0
8
0
Order By: Relevance
“…A recent study of HRGC as applied to the analysis of turbine engine fuels and other complex organic mixtures [3] showed that attention must be given to every aspect of the chromatographic system to obtain high performance, well shaped elution profiles, good quantitative data, and long useful life from the chromatographic system. From a theoretical standpoint, if two different solutes have a measurable difference in their partition ratios, they can be separated with an adequately efficient column.…”
Section: Nevertheless It Was Recently Theorized [2]mentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study of HRGC as applied to the analysis of turbine engine fuels and other complex organic mixtures [3] showed that attention must be given to every aspect of the chromatographic system to obtain high performance, well shaped elution profiles, good quantitative data, and long useful life from the chromatographic system. From a theoretical standpoint, if two different solutes have a measurable difference in their partition ratios, they can be separated with an adequately efficient column.…”
Section: Nevertheless It Was Recently Theorized [2]mentioning
confidence: 99%
“…Also, the use of tandem dissimilar columns, "* column systems which incorporate various switching mechanisms, and the information content of this mode of gas chromatography have been investigated. Several studies [14][15][16][17][18][19] have investigated two-dimensional GC which involved dissimilar stationary phases, various forms of column switching, and backflushing to obtain *A shorter and earlier review of MDGC with respect to GC system design was presented in reference [3], pages 101 through 106.…”
Section: Review Of Literature Pertaining To Various Multidimensional mentioning
confidence: 99%
See 3 more Smart Citations